2010
DOI: 10.1155/2010/272517
|View full text |Cite
|
Sign up to set email alerts
|

Flow Cytometry and Polymerase Chain Reaction-Based Analyses of Minimal Residual Disease in Chronic Lymphocytic Leukemia

Abstract: New therapeutic strategies developed recently for chronic lymphocytic leukemia (CLL) have led to remarkable treatment response rates and complete hematological remissions. This means highly sensitive and specific techniques are increasingly needed to evaluate minimal residual disease (MRD) in CLL patients. Quantitative MRD levels can be used as prognostic markers, where total MRD eradication is associated with prolonged survival. Nowadays, PCR and flow cytometry techniques used to detect MRD in CLL patients ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Feeding the rats with the different diets did not significantly affect the pack cell volume and mean corpuscular volume values of the experimental rats when compared to the control groups and suggested that the consumption of false yam is safe and has no potential blood toxicity effect. Blood toxicity is usually accompanied with significant changes in the values of hematological parameters including fall in values of RBC, Hb and PVC due to possible suppression of erythropoietic processes of hemolysis of the available RBC and resulting in liver necrosis and anemia with changes in blood biochemicalparameters [23]. The results of these blood parameters show very low standard mean error (SEM±) and thus support their findings.…”
Section: Hematological Indices Of Albino Rats Fed Treatment Dietssupporting
confidence: 69%
“…Feeding the rats with the different diets did not significantly affect the pack cell volume and mean corpuscular volume values of the experimental rats when compared to the control groups and suggested that the consumption of false yam is safe and has no potential blood toxicity effect. Blood toxicity is usually accompanied with significant changes in the values of hematological parameters including fall in values of RBC, Hb and PVC due to possible suppression of erythropoietic processes of hemolysis of the available RBC and resulting in liver necrosis and anemia with changes in blood biochemicalparameters [23]. The results of these blood parameters show very low standard mean error (SEM±) and thus support their findings.…”
Section: Hematological Indices Of Albino Rats Fed Treatment Dietssupporting
confidence: 69%
“…Several studies have demonstrated that morphological response criteria are not sufficiently sensitive to predict outcome (Rawstron et al , ; Moreno et al , ; Böttcher et al , ) and that CLL patients who achieve an eradication of detectable MRD, determined by highly sensitive techniques, have a prolonged survival (Moreton et al , ; Hallek et al , ; Böttcher et al , ). In spite of this, the clinical role of MRD detection in CLL remains to be fully elucidated (Uhrmacher et al , ).…”
mentioning
confidence: 99%
“…A large German study (CLL3X trail) assessing MRD through MFC or real-time PCR showed similar results and no impact of disease risk on the post-transplant outcome (13). Overall, although available studies evaluating MRD in CLL are not always comparable because of the treatment protocols and methods used to evaluate the molecular disease ranging from low-sensitive techniques (two-color MFC or consensus PCR) to high sensitive ones (MFC or patient-specific PCR) (10,14), the results agree in showing that patients achieving molecular remission do better, underlying the importance to reduce disease below 1/10^4-10^5 normal cells.…”
Section: Discussionmentioning
confidence: 94%